2012
DOI: 10.5897/ajpp11.547
|View full text |Cite
|
Sign up to set email alerts
|

Qianliening capsule treats benign prostatic hyperplasia through regulating the expression of sex hormones, estrogen receptor and androgen receptor

Abstract: The objective of the study is to evaluate the effect of Qianliening capsule (QLNC) on the expression levels of serum hormones, prostatic estrogen receptor and androgen receptor in benign prostatic hyperplasia (BPH) rats, and investigate the possible molecular mechanisms mediating its anti-BPH activity. Male Sprage-Dawley (SD) rat BPH model was generated. BPH rats were orally treated with different concentrations of QLNC. Blood and the prostatic tissues of animals were obtained. The prostatic weight (PW) and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…These products together confer properties of heat-clearing, detoxification, promotion of blood circulation, removal of blood stasis, tonifying the kidney and nourishing vitality (replenishing the kidney qi in Chinese medicine) (26,27). In the past two decades, QC has been shown to have significant therapeutic effects on BPH (27–29). In clinical trials, QC markedly improved BPH symptoms, by increasing the free maximum urinary flow rate and average urinary flow rate, alleviating frequent urination and urinary urgency, and improving the dynamic index of urine flow (30).…”
Section: Introductionmentioning
confidence: 99%
“…These products together confer properties of heat-clearing, detoxification, promotion of blood circulation, removal of blood stasis, tonifying the kidney and nourishing vitality (replenishing the kidney qi in Chinese medicine) (26,27). In the past two decades, QC has been shown to have significant therapeutic effects on BPH (27–29). In clinical trials, QC markedly improved BPH symptoms, by increasing the free maximum urinary flow rate and average urinary flow rate, alleviating frequent urination and urinary urgency, and improving the dynamic index of urine flow (30).…”
Section: Introductionmentioning
confidence: 99%
“…QC are a Traditional Chinese Medicinal formulation, which has been used clinically in China for numerous years, exhibiting significant efficacy in BPH treatment (16,(30)(31)(32)(33). However, the mechanism underlying its anti-BPH activity remains to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Qianliening capsules (QC) are a Traditional Chinese Medicine and consist of a combination of rhubarb (Radix et Rhizoma Rhei), leech (Hirudo), Astragalus (Radix Astragali), Achyranthes (Radix Achyranthis bidentatae) and Dodder (Semen Cuscutae). These products together confer the QC properties of heat-clearance, detoxification, promotion of blood circulation, removal of blood stasis and tonfication of the kidney, the latter being considered to nourish vitality and referred to as replenishing the kidney qi in Chinese Medicine (29,30). It has been reported that QCs have significant therapeutic effects on BPH by improving a series of LUTS and the dynamic index of urine flow in patients with BPH (29,31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predominant actions of QC include heat-clearing and detoxification, promoting blood circulation, removing blood stasis, toning up the kidney and nourishing vitality (termed 'replenishing qi' in Chinese) (9). Our previous studies revealed that QC inhibits the proliferation of benign prostatic hyperplastia epithelial cell line 1 (BPH-1) cells, promotes their apoptosis and regulates the effects of certain cytokines (10)(11)(12)(13) to exert its therapeutic effects on BPH. However, the specific mechanisms underlying the therapeutic effectiveness of QC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%